Consent in the Presence of Force : Sexual Violence and Black Women's Survival in Antebellum New Orleans - Owens, Emily A. (Book collections on Project MUSE., 2023)
"In histories of enslavement and in Black women's history, coercion looms large in any discussion of sex and sexuality. At a time when sexual violence against Black women was virtually unregulated--even normalized--a vast economy developed specifically to sell the sexual labor of Black women. In this vividly rendered book, Emily A. Owens wrestles with the question of why white men paid notoriously high prices to gain sexual access to the bodies of enslaved women to whom they already had legal and social access"--